Evoluții în domeniul surselor standardului de viață al populației - Mărginean, Ioan; Țambrea, Narcisa; Voinea, Ion (Calitatea Vieții, 1994)
The authors take a look on changes in standard of living sources during the transition to market economy in Romania. They want to analyse the effects of these changes on well-being of the population. The conclusion is that some shifts are taking place, specially from salary to income obtained from people working on their own, but there is small effect on standard of living. The previous strong egalitarism is still in action mostly because standard of living is going down in transition period for most of the households.